Mechanisms of power, victimization and autonomy in the health care system - Takács, Erzsébet (METSZETEK Társadalomtudományi Folyóirat, 2022)
The aim of this paper is to describe power relations, doctor-patient relationships among the many ongoing changes in health care from sociological point of view. This paper is based on interviews with 17 people who work in various fields of health care. To conduct the interviews as well as to write the paper, a number of concepts and theoretical approaches were resorted to: Dominique Memmi’s ’delegated biopower’, Eve Bureau and Judith Hermann-Mesfen’s notion of ’contemporary patient’, François Dubet’s concept of institutional programme as well as results of Hungarian health sociology. The main focuses of interest of the paper are role models in health care, the characteristics and consequences of new doctor-patient relations, their manifestations in Hungary as well as potentials of defencelessness and autonomy in Hungarian health care.